PENGGUNAAN MEDIA GAMBAR DALAM MENGEMBANGKAN NILAI - NILAI AGAMA DAN MORAL PESERTA DIDIK - Fizri Via Agustina, (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2025)
Developing religious and moral values ​​to students need to do this from an early age and be done by all components of the nation such as parents, educational institutions and public. Development of religious and moral values ​​in participants education must be carried out using various media appropriate and appropriate to the conditions of students, including: using image media. By using image media It is hoped that this will have an impact on developing values religion and morals in students. This research uses qualitative approach with the type of Classroom Action Research. Research activities include planning, implementation, observation and reflection. In collecting data, the author using observation, interview and documentation methods. Meanwhile, for the analysis, descriptive analysis techniques were used qualitative. Research on the use of image media can be done develop the religious and moral values ​​of students at RA Raudhatul Huda, Wonosari Village, Bandar Lampung, it can be seen that there has been an increase in the participants' religious morality students, at the time of the pre survey in general their religious morality developed well in the pre-survey